A Critical Role for Sox9 in Notch‐Induced Astrogliogenesis and Stem Cell Maintenance123. (20th March 2013) - Martini, Simone; Bernoth, Kristina; Main, Heather; Ortega, German Dario Camargo; Lendahl, Urban; Just, Ursula; Schwanbeck, Ralf
Abstract Notch signaling is a key regulator of cell‐fate decisions and is essential for proper neuroectodermal development. There, it favors the formation of ectoderm, promotes maintenance of neural stem cells, inhibits differentiation into neurons, and commits neural progenitors to a glial fate. In this report, we explore downstream effects of Notch important for astroglial differentiation. Transient activation of Notch1 during early stages of neuroectodermal differentiation of embryonic stem cells resulted in an increase of neural stem cells, a reduction in neurons, an induction of astroglial cell differentiation, and an induction of neural crest (NC) development. Transient or continuous activation of Notch1 during neuroectodermal differentiation led to upregulation of Sox9 expression. Knockdown of the Notch1‐induced Sox9 expression reversed Notch1‐induced astroglial cell differentiation, increase in neural stem cells, and the decrease in neurons, whereas the Notch1 effects on NC development were hardly affected by knockdown of Sox9 expression. These findings reveal a critical role for Notch‐mediated upregulation of Sox9 in a select set of neural lineage determination steps controlled by Notch. STEM CELLS2013;31:741–751